Metabolism of Hyperpolarized [1-(13)C]Pyruvate in the Isolated Perfused Rat Lung – An Ischemia Study - Pullinger, B. (2012)
We report studies of the effect of ischemia on the metabolic activity of the intact, perfused lung, and its restoration after a period of reperfusion. Two groups of rat lungs were studied using hyperpolarized 1-(13)C pyruvate to compare the rate of lactate labeling, differing only in the temporal ordering of ischemic and normoxic acquisitions. In both cases, a several-fold increase in lactate labeling was observed immediately after a 25-minute ischemia event as was its reversal back to the baseline after 30–40 minutes of resumed perfusion (n=5, p < 0.025 for both comparisons). These results were corroborated by (31)P spectroscopy, and correspond well to measured changes in lactate pool size determined by (1)H spectroscopy of freeze-clamped specimens.